ANALISIS PEMANFAATAN ASET NEGARA TANPA IZIN MENURUT PANDANGAN HUKUM ISLAM: (Studi Kasus pada Kios Cinderamata kawasan kota sigli) - Lisa Nansadiqa (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2024)
This research was conductes to see how state are used without permission according to the view of islamic law, with the research location at a souvenir kiosk in the Sigli City area hereby to see what factors cause the use of state assets without permission,as well as what is the view according to islamic law regarding the use of state facilities without permissiin in the Sigli City area. The method used is to collect sources, namely, library research an using the field research method.this model can explain the use of state assets without permission according to Islamic law, of caourse it is not recommended in Islam, but due to the economic crisis and the lack of employment in Pidie Regency, the community sees the opportunities that exist, but this is also not justified therefore